Sex Differences in Mental Stress‐Induced Myocardial Ischemia in Patients With Coronary Heart Disease. Issue 9 (September 2016) - Vaccarino, Viola; Wilmot, Kobina; Mheid, Ibhar Al; Ramadan, Ronnie; Pimple, Pratik; Shah, Amit J.; Garcia, Ernest V.; Nye, Jonathon; Ward, Laura; Hammadah, Muhammad; Kutner, Michael; Long, Qi; et al.
Abstract : Background: Emerging data suggest that young women with coronary heart disease (CHD) are disproportionally vulnerable to the adverse cardiovascular effects of psychological stress. We hypothesized that younger, but not older, women with stable CHD are more likely than their male peers to develop mental stress‐induced myocardial ischemia (MSIMI). Methods and Results: We studied 686 patients (191 women) with stable coronary heart disease (CHD). Patients underwent 99m Tc‐sestamibi myocardial perfusion imaging at rest and with both mental (speech task) and conventional (exercise/pharmacological) stress testing. We compared quantitative (by automated software) and visual parameters of inducible ischemia between women and men and assessed age as an effect modifier. Women had a more‐adverse psychosocial profile than men whereas there were few differences in medical history and CHD risk factors. Both quantitative and visual indicators of ischemia with mental stress were disproportionally larger in younger women. For each 10 years of decreasing age, the total reversibility severity score with mental stress was 9.6 incremental points higher (interaction, P <0.001) and the incidence of MSIMI was 82.6% higher (interaction, P =0.004) in women than in men. Incidence of MSIMI in women ≤50 years was almost 4‐fold higher than in men of similar age and older patients. These results persisted when adjusting for sociodemographic and medical risk factors, psychosocial factors, and medications. There were no significant sex differences in inducible ischemia with conventional stress. Conclusions: Young women with stable CHD are susceptible to MSIMI, which could play a role in the prognosis of this group.